Social categorization and individuation in the own-age bias - Craig, Belinda; Thorne, E. (John Wiley & Sons Ltd., 2019)
Young adults recognize other young adult faces more accurately than older adult faces, an effect termed the own-age bias (OAB). The categorization-individuation model (CIM) proposes that recognition memory biases like the OAB occur as unfamiliar faces are initially quickly categorized. In-group faces are seen as socially relevant which motivates the processing of individuating facial features. Outgroup faces are processed more superficially with attention to category-specific information which hinders subsequent recognition. To examine the roles of categorization and individuation in the context of the OAB, participants completed a face recognition task and a speeded age categorization task including young and older adult faces. In the recognition task, half of the participants were given instructions aimed to encourage individuation of other-age faces. An OAB emerged that was not influenced by individuation instructions, but the magnitude of the OAB was correlated with performance in the categorization task. The larger the categorization advantage for older adult over young adult faces, the larger the OAB. These results support the premise that social categorization processes can affect the subsequent recognition of own- and other-age faces, but do not provide evidence for the effectiveness of individuation instructions in reducing the OAB.